Optimalisasi Era Digitalisasi Bagi Remaja untuk Meningkatkan Ekonomi Masyarakat Gabusbanaran Tembelang Jombang - Waslah Waslah; M Fahmi Ulum; Angela M Mardiana; Herning Setiowati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2023)
From the observations that have been carried out and interviews with village leaders. There are several community problems in uneven economic conditions, among others, there is still a lot of community potential that has not been explored. The need for innovation in processing agricultural products in Gabusbanaran village and public awareness to advance residents' incomes with non-seasonal fixed incomes so as to stabilize people's incomes. The purpose of this training is to increase the knowledge of IPNU and IPPNU members and their merchants (MSMEs) in Gabusbanaran Village about new innovations in how to sell on social media, empowering IPNU and IPPNU members and merchant mothers to achieve mutual prosperity and increase the utilization of Gabusbanaran Village produce. The method of community service activities is through seminar training for Village Youth Empowerment for Optimizing the Digitalization Era along with providing product ideas for selling by introducing the way of making candied products from watermelon skin